2004
DOI: 10.1242/jeb.01317
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterisation of theAnophelesleucokinins and their cognate G-protein coupled receptor

Abstract: Drosophila leucokinin was also found to activate the Anopheles receptor with a similar EC 50 value to Anopheles leucokinin I. However, when the Anopheles peptides were applied to the Drosophila receptor, only Anopheles leucokinin I and II elicited a rise in [Ca 2+ ] i . This suggests that the Anopheles receptor has a broader specificity for leucokinin ligands than the Drosophila receptor.Antisera raised against the Anopheles receptor identified a doublet of approx. 65 and 72·kDa on western blots, consistent wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 31 publications
1
39
0
1
Order By: Relevance
“…Our observations of A. aegypti tubules, together with the discovery of this ouabain transport system in another dipteran Drosophila (Torrie et al, 2004), suggest P-type Na Another intriguing aspect of stellate cell morphology that lends support for a greater functional role was their slender, elongated, cellular extensions that share a substantial area of contact with up to four adjacent principal cells (Fig.·2D,E, Fig.·3E,F). Although this was also noted in a previous scanning electron microscopy study (Satmary and Bradley, 1984a), stellate cells, until now, were dismissed as being vital to secretory function because they constitute only between 16-26% of the total cell number of tubules (Satmary and Bradley, 1984b;Cabrero et al, 2004), and the dimensions of their cellular extensions and contact area with principal cells were underestimated utilizing light microscopy . Instead, we propose that stellate cells themselves, or the interface between stellate and principal cells, could be the site for Cl -transport, a major aspect of the ion secretory mechanism that remains unresolved.…”
Section: Malpighian Tubulesmentioning
confidence: 81%
See 1 more Smart Citation
“…Our observations of A. aegypti tubules, together with the discovery of this ouabain transport system in another dipteran Drosophila (Torrie et al, 2004), suggest P-type Na Another intriguing aspect of stellate cell morphology that lends support for a greater functional role was their slender, elongated, cellular extensions that share a substantial area of contact with up to four adjacent principal cells (Fig.·2D,E, Fig.·3E,F). Although this was also noted in a previous scanning electron microscopy study (Satmary and Bradley, 1984a), stellate cells, until now, were dismissed as being vital to secretory function because they constitute only between 16-26% of the total cell number of tubules (Satmary and Bradley, 1984b;Cabrero et al, 2004), and the dimensions of their cellular extensions and contact area with principal cells were underestimated utilizing light microscopy . Instead, we propose that stellate cells themselves, or the interface between stellate and principal cells, could be the site for Cl -transport, a major aspect of the ion secretory mechanism that remains unresolved.…”
Section: Malpighian Tubulesmentioning
confidence: 81%
“…Cabrero et al (Cabrero et al, 2004), examining alkaline phosphatase expression in several genera of dipterans, confirmed the absence of stellate cells in both Anopheles and Aedes mosquito lower tubules and suggested a role in reabsorption for this enzyme found only in this segment of dipteran Malpighian tubules. The lower, proximal segment of both D. melanogaster and Rhodnius prolixus has been determined to be involved in the reabsorption of K + from the tubule lumen (Maddrell and Phillips, 1975;Maddrell, 1978;O'Donnell and Maddrell, 1995;Haley and O'Donnell, 1997;Rheault and O'Donnell, 2001).…”
Section: Malpighian Tubulesmentioning
confidence: 88%
“…1), especially in relation to signalling cascades initiated by neuropeptides . Mosquito tubules also contain principal and stellate cells, and research into cell signalling mechanisms in mosquito tubules has revealed important insights into control of epithelial function in blood-feeding insects via both cell types (Coast et al, 2005;Kersch and Pietrantonio, 2011;Pollock et al, 2004;Radford et al, 2004;Schepel et al, 2010).…”
Section: The Malpighian Tubules As Stress Sensorsmentioning
confidence: 99%
“…cAMP and cGMP have been shown to play a role in stellate cells (Kerr et al, 2004), although the endogenous pathways for cAMP and cGMP are not known for this tubule cell type. Recent research, however, has demonstrated that cGMP acting through DG1 (but not DG2) can inhibit transepithelial responses induced by both tyramine and D. melanogaster leucokinin (Ruka et al, 2013), both of which increase calcium signalling and chloride conductance (Blumenthal, 2003;Cabrero et al, 2013;O'Donnell et al, 1996;Radford et al, 2004;Terhzaz et al, 1999). Thus, a yet-unidentified inhibitory process for tyramine and D. melanogaster leucokinin signalling in stellate cells is cGMP/DG1-mediated.…”
Section: Camp Signallingmentioning
confidence: 99%
“…Our group's work, however, has shown that renal function can also be studied to great advantage in Drosophila (Dow and Davies, 2001;Dow and Davies, 2003;Dow and Davies, 2006). The sequenced genome allowed the rapid identification of genes encoding diuretic neuropeptides (Cabrero et al, 2002;Coast et al, 2001;Kean et al, 2002;Terhzaz et al, 1999) and their receptors (Johnson et al, 2005;Radford et al, 2002), often before it proved possible in nonmodel organisms, and indeed these studies paved the way for similar work in other insects (Radford et al, 2004).…”
Section: The Need For Model Organismsmentioning
confidence: 92%